Cerebral Blood Flow Autoregulation in Offspring From Experimentally Preeclamptic Rats and the Effect of Age - Whitaker, Emmett E.; Johnson, Abbie C.; Tremble, Sarah M.; McGinn, Conor; DeLance, Nicole; Cipolla, Marilyn J. (Frontiers in Physiology, 2022)
Preeclampsia is a hypertensive disorder of pregnancy that causes significant, long term cardiovascular effects for both the mother and offspring. A previous study demonstrated that middle cerebral arteries in offspring from an experimental rat model of preeclampsia were smaller, stiffer, and did not enlarge over the course of maturation, suggesting potential hemodynamic alterations in these offspring. Here we investigated the effect of experimental preeclampsia on cerebral blood flow autoregulation in juvenile and adult offspring that were born from normal pregnant or experimentally preeclamptic rats. Relative cerebral blood flow was measured using laser Doppler flowmetry, and cerebral blood flow autoregulation curves were constructed by raising blood pressure and controlled hemorrhage to lower blood pressure. Immunohistochemistry was used to assess middle cerebral artery size. Heart rate and blood pressure were measured in awake adult offspring using implanted radiotelemetry. Serum epinephrine was measured using enzyme-linked immunosorbent assay. Offspring from both groups showed maturation of cerebral blood flow autoregulation as offspring aged from juvenile to adulthood as demonstrated by the wider autoregulatory plateau. Experimental preeclampsia did not affect cerebral blood flow autoregulation in juvenile offspring, and it had no effect on cerebral blood flow autoregulation in adult offspring over the lower range of blood pressures. However, experimental preeclampsia caused a right shift in the upper range of blood pressures in adult offspring (compared to normal pregnant). Structurally, middle cerebral arteries from normal pregnant offspring demonstrated growth with aging, while middle cerebral arteries from experimentally preeclamptic offspring did not, and by adulthood normal pregnant offspring had significantly larger middle cerebral arteries. Middle cerebral artery lumen diameters did not significantly change as offspring aged. Serum epinephrine was elevated in juvenile experimentally preeclamptic offspring, and a greater degree of hemorrhage was required to induce hypotension, suggesting increased sympathetic activity. Finally, despite no evidence of increased sympathetic activity, adult experimentally preeclamptic offspring were found to have persistently higher heart rate. These results demonstrate a significant effect of experimental preeclampsia on the upper range of autoregulation and cerebrovascular structure in juvenile and adult offspring that could have an important influence on brain perfusion under conditions of hypo and/or hypertension.